House Prices, Home Equity Borrowing, and Entrepreneurship - Corradin, Stefano; Popov, Alexander (Review of Financial Studies, 2015)
This paper shows that housing wealth helps alleviate credit constraints for potential entrepreneurs by enabling home owners to extract equity from their property and invest it in their business. Using a large U.S. individual-level survey dataset for the 1996–2006 period, we find that a 10% increase in home equity raises the share of individuals who transition into self-employment each year from 1% to 1.07%. Our results persist when we use proxies for aggregate housing demand shocks and for the topological elasticity of housing supply to generate variation in home equity that is orthogonal to entrepreneurial choice.